2001
DOI: 10.1016/s0022-5347(05)66066-1
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Sparing Surgery for Renal Tumors: Indications, Techniques and Outcomes

Abstract: Nephron sparing surgery provides effective therapy for patients in whom preservation of renal function is a relevant clinical consideration. The importance of meticulous operative technique for achieving acceptable oncological and functional outcomes is emphasized. Accumulating data in appropriately select patients suggest a long-term functional advantage gained by the maximal preservation of unaffected renal parenchyma without sacrificing cancer control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
349
2
27

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 813 publications
(385 citation statements)
references
References 132 publications
7
349
2
27
Order By: Relevance
“…15 The local tumour recurrence was 3.5%. Similar results were reported in a meta-analysis 16 looking at a series of patients undergoing open partial nephrectomy (OPN) from 1980 to 2000. A study that compared 100 cases of laparoscopic partial nephrectomy (LPN) with OPN concluded that OPN remains the standard of care for SRM.…”
Section: Fundingsupporting
confidence: 80%
“…15 The local tumour recurrence was 3.5%. Similar results were reported in a meta-analysis 16 looking at a series of patients undergoing open partial nephrectomy (OPN) from 1980 to 2000. A study that compared 100 cases of laparoscopic partial nephrectomy (LPN) with OPN concluded that OPN remains the standard of care for SRM.…”
Section: Fundingsupporting
confidence: 80%
“…All are similarly effective, but carry their own morbidity, with a complication rate up to 30% in several series [6]. Some patients have contraindications to general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Nephron-sparing surgery (NSS) is the mainstay of treatment for small renal cell carcinoma due to the well-preserved renal function and comparable oncological outcome to radical nephrectomy (RN) [1,2,3,4]. However, NSS can be technically challenging and morbidity can be high, especially in patients with large, centrally located or endophytic tumors.…”
Section: Introductionmentioning
confidence: 99%